1988
DOI: 10.1002/jcc.540090802
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of small silicon and aluminum clusters

Abstract: Small Sin and Al, clusters (n = 3-10) were studied with the semiempirical molecular orbital method (MO) method SINDO1. For each n, various structures were optimized to determine the most stable structure. To obtain good qualitative agreement with available ab initio calculations d orbitals had to be omitted from the basis set. Both silicon and aluminum tend to build three-dimensional structures rather than two-or one-dimensional structures, except for n = 3 or 4. The structure growth was studied by approaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…DFT calculation shows that the most stable form of Al 3 is an equilateral triangle, in agreement with the work of Pettersson et al 1 For Al 4 the planar rhombus ͑D 2h ͒ conformation is found to be more stable than the pyramidal form ͑C 3v ͒, in agreement with Koutecky et al 43 and Pettersson et al 1 In the case of Al 5 , Jug et al 44 found the pyramidal form to be the most stable, whereas Petterson et al 1 and Yang et al 9 found the planar ͑C 2v ͒ form to be more stable than the pyramidal form. The DFT calculations for Al 5 are consistent with the works of Yang et al 9 In addition, Pettersson et al 1 found that in the case of Al 6 the octahedron is the most stable form, whereas Upton 2 found a distorted octahedron to be the most stable.…”
Section: A Heats Of Formation and Geometry Of Clusterssupporting
confidence: 86%
“…DFT calculation shows that the most stable form of Al 3 is an equilateral triangle, in agreement with the work of Pettersson et al 1 For Al 4 the planar rhombus ͑D 2h ͒ conformation is found to be more stable than the pyramidal form ͑C 3v ͒, in agreement with Koutecky et al 43 and Pettersson et al 1 In the case of Al 5 , Jug et al 44 found the pyramidal form to be the most stable, whereas Petterson et al 1 and Yang et al 9 found the planar ͑C 2v ͒ form to be more stable than the pyramidal form. The DFT calculations for Al 5 are consistent with the works of Yang et al 9 In addition, Pettersson et al 1 found that in the case of Al 6 the octahedron is the most stable form, whereas Upton 2 found a distorted octahedron to be the most stable.…”
Section: A Heats Of Formation and Geometry Of Clusterssupporting
confidence: 86%
“…It goes back to the middle of the 1980s that a number of theoretical studies of Al clusters have been carried out by different groups [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39]. These studies range from the simple jellium model [20] where the cluster geometry is ignored, to a number of models where the geometry explicitly enters into the picture including semiempirical molecular orbital calculations [21], quantum molecular dynamics [26,27,28,29,31], quantum-mechanical calculations based on quantumchemical [22,23,24] and density-functional [25,26,27,28,29,30,31,32,33] theories (DFT) within local density or local spin-density approximations, molecular dynamics and Monte Carlo simulations based on empirical model potentials [34,35,36,37,38,39]...…”
Section: A Aluminium Clustersmentioning
confidence: 99%
“…Our results are in agreement with previous Hartree-Fock [23] and DFT [30] studies which indicate the rhombus structure as the absolute minimum in the potential energy surface. A Generalized Valence Bond investigation [9] gives a three-dimensional deformed rhombus as the ground state, whereas semiempirical computations prefer the trigonaI pyramid coming from a Jahn-Teller distortion of a tetrahedral structure [24].…”
Section: A14 A1 + A17mentioning
confidence: 99%